2008
DOI: 10.1152/ajpheart.00918.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of endothelin signaling modifies membrane type 1 matrix metalloproteinase activity during ischemia and reperfusion

Abstract: Deschamps AM, Zavadzkas J, Murphy RL, Koval CN, McLean JE, Jeffords L, Saunders SM, Sheats NJ, Stroud RE, Spinale FG. Interruption of endothelin signaling modifies membrane type 1 matrix metalloproteinase activity during ischemia and reperfusion. Am J Physiol Heart Circ Physiol 294: H875-H883, 2008. First published December 7, 2007 doi:10.1152/ajpheart.00918.2007.-The matrix metalloproteinases (MMPs), in particular, membrane type 1 MMP (MT1-MMP), are increased in the context of myocardial ischemia and reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…A potential connection between ET-1 and MMP induction in pathological disease states has been observed from investigations of tumor cell invasion, cancerous growth, arthritis, and vascular remodeling (1, 2, 5, 45, 46). The recent study by Deschamps et al (17) found ET A selective receptor antagonism attenuated the ET-1-mediated increase in membrane type 1 MMP activity following ischemia-reperfusion. However, this study did not address changes in overall LV function secondary to ET-1-mediated myocardial remodeling.…”
Section: Metalloproteinase Activation and Collagen Degradation Postfimentioning
confidence: 95%
“…A potential connection between ET-1 and MMP induction in pathological disease states has been observed from investigations of tumor cell invasion, cancerous growth, arthritis, and vascular remodeling (1, 2, 5, 45, 46). The recent study by Deschamps et al (17) found ET A selective receptor antagonism attenuated the ET-1-mediated increase in membrane type 1 MMP activity following ischemia-reperfusion. However, this study did not address changes in overall LV function secondary to ET-1-mediated myocardial remodeling.…”
Section: Metalloproteinase Activation and Collagen Degradation Postfimentioning
confidence: 95%
“…A sterile microdialysis probe containing a 4-mmlong membrane (20 kDa, CMA/Microdialysis, North Chelmsford, MA) was placed into the LV midmyocardium in two regions: the main region served by the first and second obtuse marginal branches of the LCx (LCx region) and the region served by the diagonal branches of the LAD (LAD region). These microdialysis probes have been successfully placed in the LV of animals and patients previously to measure local bioactive signaling and MMP activity (5,6,22,38). Moreover, it has been demonstrated that this surgical approach for placement of the microdialysis probe was not associated with alterations in blood flow or extravasation of red blood cells, did not change local bioactive peptide levels, and was not associated with an acute inflammatory response (5,6).…”
Section: Methodsmentioning
confidence: 99%
“…One of the best-characterized and prototypical membrane type MMPs is membrane type-I MMP (MT1-MMP), which has been reported to be increased in abundance and activity in the context of I/R (5). Moreover, studies (3,6) have established that MT1-MMP is induced by upstream bioactive molecules such as PKC and endothelin. However, whether and to what degree MT1-MMP is induced within the remote region before I/R, and whether it would be increased in magnitude after the I/R event, remain to be demonstrated.…”
mentioning
confidence: 99%
“…Initial cleavage of collagen by collagenase is necessary in order for gelatinases to complete degradation. Thus it is possible that other MMPs, including collagenases, may continue to be affected in the bosentan-treated AV fistula hearts (10,12). Regardless, it would appear that this relative protection against adverse extracellular matrix remodeling persisted beyond the acute effects of ET-1 antagonism on MMP activation, given the attenuated LV chamber dilatation seen in the 14-day bosentan-treated group.…”
Section: Myocardial Collagen Content Postfistulamentioning
confidence: 99%